2013
DOI: 10.4102/sajcd.v60i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear function in patients with chronic kidney disease

Abstract: Objective: To evaluate cochlear functioning in patients (18 - 45 years old) with varying stages of chronic kidney disease (CKD). Using purposive sampling, 50 participants, 10 in each of the 5 stages of CKD, were selected and underwent pure tone audiometric testing and distortion product otoacoustic emissions (DPOAEs).Results: Significant differences (p<0.05) were found between pure tone audiometry and DPOAEs in detecting early cochlear dysfunction in the high-frequency range in stages 3 (6 000/5 000 Hz; p=0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
(16 reference statements)
1
11
0
1
Order By: Relevance
“…The kidney and cochlea have common antigenicity and similar physiologic mechanisms involving the transport of fluid and electrolytes, which might explain the hearing loss in patients with kidney disease [21]. Some possible aetiological factors related to hearing loss in kidney failure patients have also been reported, including electrolyte disturbances, hypertension, the use of ototoxic drug and hemodialysis treatment [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The kidney and cochlea have common antigenicity and similar physiologic mechanisms involving the transport of fluid and electrolytes, which might explain the hearing loss in patients with kidney disease [21]. Some possible aetiological factors related to hearing loss in kidney failure patients have also been reported, including electrolyte disturbances, hypertension, the use of ototoxic drug and hemodialysis treatment [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…al. [45] reported that cochlear function in patients with CKD could be affected by elevated electrolyte, urea and creatinine levels, concomitant conditions such as hypertension, and ototoxic drugs such as furosemide.…”
Section: Discussionmentioning
confidence: 99%
“…al. [46] reported that cochlear function in patients with CKD could be affected by elevated electrolyte, urea and creatinine levels, concomitant conditions such as hypertension, and ototoxic drugs such as furosemide.…”
Section: Discussionmentioning
confidence: 99%